Fatwa MUI tentang Khitan Perempuan - M. Asrorun Ni'am Sholeh (AHKAM : Jurnal Ilmu Syariah, 2012)
Abstract: The MUI Fatwa about Female Circumcision. The issue of female circumcision has become a public issue following research, either independent or sponsored, repeatedly finding there to be a number of negative effects arising from allowing the enforcement of female circumcision in a number of countries. The issue of children’s and women’s protection are also often connected to the issue of the implementation of circumcision, especially in relation to children’s rights and women’s reproductive rights. This study finds that provisions targeting female circumcision do so in an effort to protect women’s rights. This article finds that the MUI fatwa, as well as ulamas’ views on madzhab and fiqh, which regulates procedures pertaining to the implementation of female circumcision, serves to strengthen the protection of children’s rights, that is, protection from negative effects which is caused by extreme actions in the dangerous practice of circumcision.Keywords: female circumcision, MUI, fatwa, fiqh, children’s protection.Abstrak: Fatwa MUI tentang Khitan Perempuan. Masalah khitan terhadap perempuan menjadi isu publik setelah adanya pelbagai penelitian, baik yang dilakukan secara independen maupun karena ada sponsor, yang menemukan adanya pelbagai dampak negatif yang ditimbulkan dari penyimpangan pelaksanaan khitan terhadap perempuan di beberapa negara. Isu perlindungan anak dan perempuan juga sering kali dikaitkan dalam masalah pelaksanaan khitan, khususnya terkait hak anak dan hak reproduksi perempuan. Studi ini menemukan bahwa ketentuan mengenai khitan perempuan sejalan dengan upaya perlindungan terhadap hak perempuan. Fatwa MUI, sebagaimana juga pandangan ulama mazhab fikih yang mengatur tata cara pelaksanaan khitan perempuan, justru meneguhkan perlindungan terhadap hak anak, yakni perlindungan dari dampak negatif yang ditimbulkan akibat tindakan berlebihan dalam praktik khitan yang menyebabkan bahaya.Kata Kunci: khitan, perempuan, fatwa MUI, fikih, perlindungan anakDOI: 10.15408/ajis.v12i1.964